Pengaruh Total Quality Service terhadap Kepuasan Nasabah pada Bank Syariah di Bengkulu - ., Darmansyah (Jurnal Aplikasi Manajemen, 2012)
A strategy that will be successful in banking industries is to offer higher service quality to customer that occurs in the performance of the service itself. The aims of this research are: first, to examinethe simultaneous and partial significant effect between service quality and customer satisfaction of syariah bank in Bengkulu, and to analyze the dominant variable of service quality that affects customer satisfactionof syariah bank in Bengkulu as well. Convenience sampling and Accidental Sampling are used in data collection then the data are multiple linier regression. The findings of this study are: first, service qualityvariable has a positive simultanears and partial significant effect influencing customer satisfication of syariah banking in Bengkulu. This study also finds that Reliability variable is the dominant factor affecting customer satisfaction of syariah banking in Bengkulu; this means customer of syariah banks in Bengkulu views that reliability (banking staff competency) is the main indicator of service quality of syariah banks in Bengkulu. This findings give an important implication and recomendation to syariah banks in Bengkulu;syairah banks in Bengkulu should maintain and sustain reliability variable in order to increase customer satisfaction.